Implementing a daily Continuing Medical Education (CME) at a rural primary care hospital in Nepal - Gauchan, Bikash; Sherchan, Rekha; Rawal, Mangal; Shrestha, Biplav; Singh, Amul; Pandey, Mrigendra Raj; Rijal, Niranjan; Pathak, Mandeep (Journal of Karnali Academy of Health Sciences, 2021)
Background: Fostering a culture of continued learning at healthcare facilities is a global priority for healthcare systems performance, patient safety, and quality improvement. In low- and middle-income countries, continuing medical education activities are almost non-existent in rural areas and so is in Nepal. National professional academies tend to be focused almost exclusively at major teaching hospitals in urban centers. In addition to playing a central role in healthcare provision, rural district-level hospitals in Nepal are formative for many young healthcare professionals who are posted there for mandatory government service. The district hospital in Nepal thus represents an important opportunity to be a center for learning. Greater investment in these types of programs may improve healthcare worker satisfaction and retention, thereby improving access to care in these remote areas. Methods: We conducted a qualitative study to describe the implementation of a continuing medical education program at a district-level hospital in rural Nepal. The particular modalities of continuing medical education include didactic lectures, case presentations, and morbidity and mortality conferences, presented by physicians and mid-level providers. We reviewed the hospital-based CME sessions. Results: During the first twelve months of the program, 155 sessions, or 73% of scheduled sessions, were conducted as planned. Ongoing challenges to the long-term success of the program include dedicated leadership, time for session preparation and presenter mentorship, and improving participatory engagement across multiple clinician cadres. Conclusions: Building a robust continuing medical education program in rural district hospitals is feasible and has great potential as a mechanism of developing a professional and sustainable cadre of healthcare workers in these settings